The strategies of Decentralization and Hybridization in Nadine Gordimer`s July`s people - امير حسين; قاسم سرحان (آداب الكوفة)
The dichotomy of centre vs periphery is a central idea in postcolonial theory and an important model to describe the relationship between colonizer and colonized. The aim of this paper is to examine the dichotomy of centre and periphery in postcolonial theory and how this dialectic is manifested in July's People by the South African prolific writer Nadine Gordimer. The African novel is an important off shoot of postcolonial novel since it documents the native`s struggle to restore their lost identities. South African novel written by white authors is a unique version of this trend of fiction since it dramatizes the awkward ambivalent experience of white authors being torn between two opposing traditions : the European and the indigenous. The dichotomy of centre and  periphery becomes subject to modification and revision in the newly born multicultural society especially after the apartheid.